The impact of the internet on Hungarian food consumers’ ways of seeking information from the aspect of health awareness - Fehér, András (Applied Studies in Agribusiness and Commerce, 2015)
One of the main components of healthy lifestyle is proper diet. When putting together one’s diet, lots of information are needed in order to be able to pick from various foods which contribute to converting to a healthier lifestyle and maintaining it. The main purpose of this study is to determine and show examples of the characteristics of online marketing which could help consumers in the conscious conversion to healthy lifestyle. Of the various factors, great emphasis is placed on online health-related information. Based on the research findings, it can be concluded that healthy lifestyle-related information has a significant role in online sources. Consequently, Internet can be regarded as a preferred source of information in terms of the conscious converting to healthy lifestyle.